Implementasi Konvensi Internasional Perlindungan Anak Di ‎Lembaga Pembinaan Khusus Kelas II Kabupaten Karangasem - Gede Yudi Antara; Deli Bunga Saravistha (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
This study discusses the implementation of children's rights in the Convention on the Rights of the Child (KHA) in Indonesia, especially in the LPKA (Special Development Institution for Children) Class II Karangasem. Indonesia has ratified the Convention on the Rights of the Child (KHA) through Presidential Decree Number 36 of 1990 but many children still lost their rights, for example, the right to education. This study aims to identify the implementation of the Convention on the Rights of the Child (KHA) for the fulfillment of the rights of inmates LPKA Class II Karangasem. This study used an empirical legal method. The results of this study showed that some programs related to the implementation of the fulfillment of children's rights in the LPKA Class II Karangasem are part of an effort to support the government in implementing the Convention on the Rights of the Child which has been ratified in Indonesia in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law Number 22 of 2022 concerning Corrections. Besides, this program is the duty and function of the Special Development Institution for Children in fostering the children in order to improve themselves to be good citizens again